Evaluation and Classification of Groundwater quality for suitability of Drinking and irrigation Purposes: A case Study in the Zamzam Region. - Amshaher عمران علي حمد; Ataf سالم فرج مفتاح (Journal of Pure & Applied Sciences, 2021)
Given This study has been conducted in December 2019 to find out the suitability of groundwater in the Wadi Zamzam area for drinking and irrigation according to the most common classification systems. Water samples were collecting from eight wells and analyzed determine the physical and chemical properties. Various water character indices like , electrical conductivity (EC) , total dissolved solids (TDS), total hardness( TH) , sodium adsorption ratio( SAR) potential of hydrogen ( PH)percent sodium (Na%) magnesium hazard ratio (Mg %) ,residual sodium carbonate (RSC) and potential salinity (PS) have been calculated for each water sample to identify the irrigation suitability standard . The results showed that the water are unsuitable for drinking use since all values were higher than the parameters limited of world health organization .On the basis of TH , all the samples are within the range of very hard ,While TDS , moderate to extreme saline . The results also showed that the samples of wells 5, 6, 8are located within C3-S1 while the rest of samples are located within C4S1 according to USDA .Either, all samples have high impact on sensitive crops based on chlorine toxicity. Finally, there is no alkali risk in all samples of wells based on Eaton classification (1950).